Upaya Meningkatkan Kemampuan Menyebutkan Bilangan 1 - 20 Melalui Bermain Kartu Angka Pada Anak Didik Kelompok B Semester 1 TK Asri Rowobungkul Kecamatan Ngawen Kabupaten Blora Tahun 2015/2016. - WATI, Wati; , Drs. Sutan Syahrir Zabda, SH,MH (2015)
This research aims to improve ability mention numbers 1-20 through play card numbers at the students group B TK Asri Rowobungkul districts Ngawen Blora year 2015/2016. The subjects in this study were students in kindergarten children Asri Rowobungkul. Implementation of this learning with action learning by playing activities card numbers. The method used is classroom action research, which consists of 2 cycles of learning. Subjects were students of kindergarten children Asri Rowobungkul totaling 25 Children. Data analysis using comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle, and a qualitative descriptive analysis of the results of observation by comparing the results of observation and reflection on Pre-Cycle, Cycle I and Cycle II. The conclusion of this study is, through playing cards numbers can improve the ability to mention numbers 1-20 for students in group B the first semester of kindergarten Asri Rowobungkul districts Blora district Ngawen year 2015/2016. Improving the ability of the students is done by using the card number. The learning is done by studying in groups, and each group doing the throwing game card numbers. After the course of this research, quantitative ability mentioned numbers 1 to 20 for kindergartners Asri Rowobungkul Ngawen the District has increased very well. In the initial condition (pre-cycle) capability mentioned numbers 1 to 20 in the classical children reached 58.80%, while in the second cycle showed the ability mentioned numbers 1 to 20 children in classical amounted to 93.40%. From these data it can be concluded that, overall, there is an increased ability mentioned numbers 1 to 20 children by 34.60%.